SIMULASI PRODUKSI HIJAUAN PADA TIPE UNIT SISTEM TIGA STRATA YANG BERBEDA - Anak Agung Oka; Ambius Anton; Ni Putu Sarini; Siswanto Siswanto (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2018)
Nowadays, availability of forage for cattle and other animal protein resources getting less and less due to land changing functions. This will lead to increase in land price, decrease in animal productivities the will end on sustainability of the animal husbandry business. In Bali, farmers applied a Three Strata Forage System to provide forage along dry and rainy seasons. This study purpose was to find out forage production from four types but similar size of land (1 ha) which applied in that system, that were Type A (rectangle: 200 m x 50 m), Type B (L Form: 4 x (50 x 50 m), Type C (rectangle: 125 m x 80 m) and Type D (squares: 100 m x 100 m). This simulation showed that the forage production of the land was 14.533,805 ton DM/year for type A and B; 14.301,434 ton DM/year for Type C : and 14.276,171 ton/DM/year for Type D. It can be concluded that the land in similar size but differ in shape or type produce different quantity of forages. And addition forage production and carrying capacity were estimated below of recommended the three strata forage system. Keywords: Forages, production, three strata forage system